Ferulic Acid Ameliorates L-Methionine-Induced Hyperhomocysteinemia in Rats - Sunita Bhise; Urmila Aswar; Akash Jadhav; Manoj Aswar; Ankit Ganeshpurkar (Drugs and Drug Candidates)
Background/Objectives: Elevated plasma homocysteine levels constitute a risk factor for vascular and cardiovascular disorders. Ferulic acid (FA), a polyphenol is tested on L-methionine-induced hyperhomocysteinemia (hHcy). The present study investigated the protective effect of ferulic acid (FA) on hyperhomocysteinemia (hHcy) induced changes in hemodynamic, biochemical, anti-oxidant, anti-inflammatory parameters as well as histopathological changes in abdominal aorta and heart. Methodology: The Wistar rats were divided into six groups (n = 6) and treated orally for 36 days. The rats were treated with Met (1 gm/kg) to induce Hcy. They were treated with either standard (Vit. B12 + Folic acid; 15 + 70 mg) or test FA (20/40/60 mg/kg, respectively) post-Met treatment. Homocysteine, cholesterol, lactate dehydrogenase (LDH), creatinine kinase (CK-MB), and liver enzymes were estimated in blood followed by the measurement of hemodynamic parameters. The liver was estimated for antioxidant parameters and nitric oxide (NO). Heart and abdominal aorta were studied histopathologically. Result: Diseased rats showed increased Hcy, cholesterol, LDH, CK-MB, alanine transaminase (ALT), aspartate transaminase (AST), malondialdehyde (MDA), NO, and reduced glutathione (GSH). Following FA treatment, these parameters returned to normal. Atherosclerotic lesions in the aorta were observed in the hHcy group; however, in the FA treatment groups, they were lessened. Conclusions: Ferulic acid reduces oxidative and nitrosive stress, thereby reducing hypercyteinemia and improving the lipid profile. It might be acting by increasing the activity of methylation dependent on S-adenosylmethionine (SAM)/S-adenosylhomocysteine (SAH), which in turn prevents the formation of Hcy and reduces hHcy. The docking study supports these findings.